EFEKTIVITAS BIMBINGAN PERKAWINAN KECANTOL KAMU (KELAS CALON PENGANTIN ONLINE-OFFLINE KARANGANOM MAJU UNGGUL) TERHADAP KESIAPAN CALON PENGANTIN DI KUA KECAMATAN KARANGANOM KLATEN TAHUN 2021-2023 - Taufiqurrahman, T; Baehaqi, B; Syamsuddin, S (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
The success of marital life depends on the readiness of marriage which consists of psychological readiness, physical readiness, material readiness, and readiness of knowledge about marriage. That is why the Ministry of Religion of the Republic of Indonesia issued the Decree of the Director General of Islamic Community Guidance Number 172 of 2022 which requires prospective brides and grooms to take marriage guidance. Therefore, the Karanganom KUA created the Kecantol Kamu marriage guidance program (Karanganom Maju Unggul Online-Offline Prospective Bride Course) as a step to provide provisions for prospective brides and grooms in realizing a household that is sakinah, mawadah and rahmah. This research is a field research. This research was conducted at the Religious Affairs Office (KUA) of Karanganom District, Klaten in February - March 2024. Data collection using interview, observation and documentation methods. The subjects of this study were the Head of the KUA Karanganom and the Islamic Religious Counselor of the KUA Karanganom. The research informants were participants in the Kecantol Kamu marriage guidance and facilitators of the Kecantol Kamu marriage guidance of the KUA Karanganom. Data analysis uses data reduction techniques, data display, and conclusion drawing/verification. To test the validity of the data, the Credibility, Transferability, Dependability, and Confirmability test techniques are used. Based on the results of the study, the author concludes: First, the implementation of the Kecantol Kamu marriage guidance at the KUA Karanganom in 2021 - 2023 has been in accordance with the technical instructions for implementing marriage guidance. Second, the Kecantol Kamu marriage guidance at the KUA Karanganom is effective in providing conceptual and mental readiness to prospective brides and grooms in entering the marital lifee, the Kecantol Kamu marriage guidance at the KUA Karanganom is also effective in reducing the divorce rate.